If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-28-4m=-2m-8(m-1)
We move all terms to the left:
-28-4m-(-2m-8(m-1))=0
We calculate terms in parentheses: -(-2m-8(m-1)), so:We get rid of parentheses
-2m-8(m-1)
We multiply parentheses
-2m-8m+8
We add all the numbers together, and all the variables
-10m+8
Back to the equation:
-(-10m+8)
-4m+10m-8-28=0
We add all the numbers together, and all the variables
6m-36=0
We move all terms containing m to the left, all other terms to the right
6m=36
m=36/6
m=6
| 11-16x=10x-3 | | –3.5(2–3n)–2.5=n | | -8y+3(y-3)=21 | | 5x^2+3=3x | | 7n-5=9n+12 | | 5+7(6-6x)=299 | | 8-8a=-3a-2 | | -16+5x-7+8=1+3x | | 7y/3=49 | | -2(7m+2)=-6(6m-3) | | -10=x+4x | | 6(6x+6)=-180 | | 35=-8(1-6a)+5(6a-7) | | w-8.55=4.3 | | 5x+3=3+7 | | u+6.31=9.18 | | 5x+3=3+17 | | v+4.5=9.46 | | 2x+6-5x+3=-8 | | 11/15=w+8/15 | | -8=g+-16 | | 226=-y+25 | | w-9.65=7.1 | | 176-v=129 | | 8-3x÷5=x | | u+2.55=8.61 | | 1+1x=2x-8 | | 12=k+17 | | 12-w=266 | | 2x^2+12x+130=0 | | 4(x-2)^2-9=11 | | 37=-v+191 |